2019
DOI: 10.1002/job.2355
|View full text |Cite
|
Sign up to set email alerts
|

Transformational leadership and creativity: A meta‐analytic review and identification of an integrated model

Abstract: Summary We conduct a meta‐analytic review that yields important insights about the existing research on transformational leadership and creativity. Additionally, we propose and test an integrated model using meta‐analytic structural equation modeling (MASEM) and full information MASEM (FIMASEM) techniques to better understand the intervening mechanism through which transformational leadership acts on creativity. The results of the meta‐analysis of 127 studies show that most of the bivariate relationships among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
112
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(124 citation statements)
references
References 244 publications
(371 reference statements)
8
112
0
4
Order By: Relevance
“…Previous studies explored the relationship between transformational leadership and follower creativity and have identified several moderators and mediators (e.g., Jaiswal & Dhar, 2016; Zhang, Sun, Jiang, & Zhang, 2019; for an overview, see Hughes, Lee, Tian, Newman, & Legood, 2018). However, findings regarding the direct impact of transformational leadership on creativity were mixed (Koh, Lee, & Joshi, 2019). One potential reason for these inconsistencies is the nature of the task, which was ignored in most studies and may have varied largely (Herrmann & Felfe, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies explored the relationship between transformational leadership and follower creativity and have identified several moderators and mediators (e.g., Jaiswal & Dhar, 2016; Zhang, Sun, Jiang, & Zhang, 2019; for an overview, see Hughes, Lee, Tian, Newman, & Legood, 2018). However, findings regarding the direct impact of transformational leadership on creativity were mixed (Koh, Lee, & Joshi, 2019). One potential reason for these inconsistencies is the nature of the task, which was ignored in most studies and may have varied largely (Herrmann & Felfe, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…According to [74], the idea of motivation is known as "the set of reasons why people behave in the ways they do", for example, intrinsic motivation is "the motivational state in which the employees are driven by their interests in the work rather than a contract-forrewards approach to completing a task" [24]. A study by Koh et al [51] identified that intrinsic motivation is highly influenced by the transformational leadership, as the transformational leader guides and supports effectively, self-motivation to be an effective and beneficial part of an organization increases as well.…”
Section: Transformational Leadership and Intrinsic Motivationmentioning
confidence: 99%
“…The team's ability to generate new and useful ideas (creativity, e.g., Amabile, 1996;West, 2002) and the subsequent process of carefully selecting and implementing these ideas (innovation; e.g., Amabile, 1988;Scott & Bruce, 1994;West, 2002) have become even more important in these recent decades of rapid technological development and intense global competition (Hennessey & Amabile, 2010;Yoshida, Sendjaya, Hirst, & Cooper, 2014). An increasing number of studies focus on what leaders can do to stimulate team creativity and innovation (see Hughes, Lee, Tian, Newman, & Legood, 2018;Lee, Koh, & Joshi, 2019;Rosing, Frese, & Bausch, 2011;Wang, Oh, Courtright, & Colbert, 2011). However, most of these studies focus on transformational leadership, and generally they do not distinguish between creativity and innovation (Hughes et al, 2018).…”
Section: Introductionmentioning
confidence: 99%